Duplication of penis - Pera Erro, Enrique; Villar, Ariel (Cirugía del Uruguay, 1976)
Duplication of penis is extremely rare. Only 60 cases can be found in the whole of bibliography. The paper contains a review thereof. -There is a communication of the first 2 cases of complete or true penis duplication in our country: there is a previous case mentioned by Bauzá of bifurcated single penis and this is classified as a case of pseudo-biphallism. -Uro-genital and general tests ( diggestive tract, bon e structures and cardiovascular) should be performed in this type of patient by reason of its frequent association with other malformations. -'he paper contains a description of operatory technique and tactics which we believe to be original, and which was applied in one of these cases. It should be pointed out that appart from a few instances of surgery on the bifid glans or scrotum this is probably the first time that systematized penectomy appears.